#
If p=2*x*² + 3x²y +3xy - 5y² Q=-5x²- 4x²y + 2xy+3xy& R= -3x²-x²y+5xy-2y² show that p+q-r=0

2
for Q is 2xy+3xy??

Log in to add a comment

for Q is 2xy+3xy??

Log in to add a comment

VERSION 1:

2x² + 3x²y +3xy - 5y² +(-5x²- 4x²y + 2xy+3y^2)-(-3x²-x²y+5xy-2y² )=2x² + 3x²y +3xy - 5y²-5x²- 4x²y + 2xy+3y^2+3x²+x²y-5xy+2y²=

2x^2-5x^2+3x^2+3x^2y-4x^2y+x^2y+

0+0+0=0 TRUE

VERSION 2:

p=2x² + 3x²y +3xy - 5y² Q=-5x²- 4x²y + 2xy+3y^2R= -3x²-x²y+5xy-2y² ==========================p+q-r=0for x^2: 2x^2-5x^2+3x^2=0

for x^2y : 3x^2y-4x^2y+x^2y=0

for xy : 3xy+2xy-5xy=0

for y^2=-5y^2+2y^2-2y^2=0

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

P = 2 x² + 3 x² y + 3 x y - 5 y²

Q = -5 x² - 4 x² y + 2 x y + 3 y²

======================= add P +Q

-3 x² - x² y + 5 x y - 2 y²

========================

Compare P+Q with R . So P+Q = R or P+Q - R = 0

Q = -5 x² - 4 x² y + 2 x y + 3 y²

======================= add P +Q

-3 x² - x² y + 5 x y - 2 y²

========================

Compare P+Q with R . So P+Q = R or P+Q - R = 0